Administrative traditions and citizen participation in public policy: a comparative study of France, Germany, the UK and Norway. (8th July 2016) - Huxley, Katy; Andrews, Rhys; Downe, James; Guarneros-Meza, Valeria
Abstract : The participation of citizens in public policy-making has become a key aim for national and supranational institutions across Europe, but the relative importance policy-makers actually accord citizen participation arguably varies due to the alternative administrative traditions within different countries. Using data drawn from a large-scale survey of senior public managers in France, Germany, the United Kingdom (UK) and Norway, we find support for the idea that administrative tradition influences the participation of citizens in public policy. We also identify key institutional factors determining the importance of citizen participation. Theoretical and practical implications of the findings are discussed.